Bacterial histo-blood group antigens contributing to genotype-dependent removal of human noroviruses with a microfiltration membrane. (15th May 2016) - Amarasiri, Mohan; Hashiba, Satoshi; Miura, Takayuki; Nakagomi, Toyoko; Nakagomi, Osamu; Ishii, Satoshi; Okabe, Satoshi; Sano, Daisuke
Abstract: We demonstrated the genotype-dependent removal of human norovirus particles with a microfiltration (MF) membrane in the presence of bacteria bearing histo-blood group antigens (HBGAs). Three genotypes (GII.3, GII.4, and GII.6) of norovirus-like particles (NoVLPs) were mixed with three bacterial strains ( Enterobacter sp. SENG-6, Escherichia coli O86:K61:B7, and Staphylococcus epidermidis ), respectively, and the mixture was filtered with an MF membrane having a nominal pore size of 0.45 μm. All NoVLP genotypes were rejected by the MF membrane in the presence of Enterobacter sp. SENG-6, which excreted HBGAs as extracellular polymeric substances (EPS). This MF membrane removal of NoVLPs was not significant when EPS was removed from cells of Enterobacter sp. SENG-6. GII.6 NoVLP was not rejected with the MF membrane in the presence of E. coli O86:K61:B7, but the removal of EPS of E. coli O86:K61:B7 increased the removal efficiency due to the interaction of NoVLPs with the exposed B-antigen in lipopolysaccharide (LPS) of E. coli O86:K61:B7. No MF membrane removal of all three genotypes was observed when S. epidermidis, an HBGA-negative strain, was mixed with NoVLPs. These results demonstrate that the location of HBGAs on bacterial cells is an important factor in determining the genotype-dependent removal efficiency of norovirus particles with the MF membrane. The presence of HBGAs in mixed liquor suspended solids from a membrane bioreactor (MBR) pilot plant was confirmed by immune-transmission electron microscopy, which implies that bacterial HBGAs can contribute to the genotype-dependent removal of human noroviruses with MBR using MF membrane. Graphical abstract: Highlights: HBGA-positive bacteria contribute to the norovirus removal with MF membrane. Cell-associated EPS with HBGA is important for removing norovirus with MF membrane. Norovirus removal with MF membrane and bacterial HBGA is genotype-dependent. HBGAs are expressed in mixed liquor suspended solids from MBR.